(untitled) (Revista Venezolana de Salud Pública, 2019)
Interpersonal relationships are fundamental for the development of society, however, disagreements, needs and particular interests are the perfect breeding ground to generate conflicts, the problem lies in the course that these conflicts can take. Daza, Pérez and López, (1998) affirm that, workplace harassment does not occur exclusively for causes directly related to the performance of work or its organization, but rather it has its origin in the interpersonal relationships established in any social entity. The objective of this research was to determine the level of knowledge that occupational health professionals have in relation to the criteria that intervene in the diagnosis of situations associated with interpersonal conflicts and workplace harassment. The methodology was based on a non-experimental field research descriptive type. The population consisted of 50 professionals who went to the registry of professionals of safety and health before the Institute of Prevention of Occupational Health and Safety in the period of January / December 2017, a non-probabilistic sample was taken as intentional, as Exclusion criteria were taken only by health professionals at work. For the data collection a questionnaire of 30 dichotomous items was designed. The results revealed that the professionals studied had difficulties in recognizing the factors that intervene in the diagnosis of the variables of interest. It is concluded that these professionals have a medium level of knowledge in relation to the elements that intervene in the diagnosis of situations associated with interpersonal conflicts and workplace harassment.